2012
DOI: 10.1111/clr.12061
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perspectives on dental implant and bone graft surgery: questionnaire‐based interview survey

Abstract: Patient expectations on implant success and predictability are high compared with their reluctance towards treatment costs and duration. Acceptance of treatment morbidity is high among patients reporting low denture satisfaction; however, minimally invasive treatment alternatives are generally preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 30 publications
3
71
0
2
Order By: Relevance
“…Most of studies aimed to assess patients’ knowledge, awareness, expectation, information level and acceptance to dental implant. The sample varied from general population without treatment need [8,9,27], patients who were seeking implants [25] and patients who had completed implant treatment [30,31]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of studies aimed to assess patients’ knowledge, awareness, expectation, information level and acceptance to dental implant. The sample varied from general population without treatment need [8,9,27], patients who were seeking implants [25] and patients who had completed implant treatment [30,31]. …”
Section: Resultsmentioning
confidence: 99%
“…The most frequently used questions were about survival time (5 studies), cost (5 studies), special oral hygiene maintenance (4 studies), information sources (3 studies) and outcome improvements like functional and aesthetical changes (4 studies). For the longevity of dental implants, Hof and coworkers [25] found that 59% of the subjects believed implants could last for a lifetime. However, the same result in Pommers’ [8] was 24% and Teppers’ [27] 34%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Hof et al 4 found that out of 150 consecutive patients seeking a dental implant, 59% expected it to last a lifetime and 31% at least ten years, and 9% shorter. Patients' estimation of the 10-year implant success rate was 84%.…”
Section: Medical/dental Evidencementioning
confidence: 99%
“…I would like to first focus on the tendency of the patients to overestimate benefits of treatment and consequently underestimate harms. There is very little specific literature, but I did find two qualitative dental studies and one medical systematic review that illustrates this bias:• Hof et al 4 found that out of 150 consecutive patients seeking a dental implant, 59% expected it to last a lifetime and 31% at least ten years, and 9% shorter. Patients' estimation of the 10-year implant success rate was 84%.…”
mentioning
confidence: 99%